Armstrong's handbook of performance management : an evidence-based guide to performance leadership - Armstrong, Michael, 1928- (New York Kogan page, 2022)
"Optimizing staff performance is a key component of achieving outstanding business results. The 7th edition of Armstrong's Handbook of Performance Management is an essential companion for improving employee and organizational performance. From performance pay and giving feedback to managing underperformers, this handbook addresses all areas of performance management to enable students and practitioners to understand how to assess, measure and improve performance. This updated 7th edition contains new chapters on the meaning and development of performance management, and covers managing and measuring performance with a remote workforce, performance leadership and multi-source feedback. Packed with examples and exercises, Armstrong's Handbook of Performance Management remains an indispensable and engaging resource for securing effective performance across all aspects of the organization. Supporting online resources include an instructor's manual, a student's manual, lecture slides, a glossary and a literature review"--
Revised edition of Armstrong's handbook of performance management, 2018.
Includes bibliographical references and index.
Keywords: Employees -- Rating of; Performance standards; Performance